Development of a Circular Nutrient Solution Management System Using a Cost Function - Yeong-Hyeon Shin; Insu Kim; Myongkyoon Yang; Young-Kyun Jang; Ronaldo B. Saludes; Hak-Jin Kim; Woo-Jae Cho (Agronomy)
In this study, an ion monitoring system using ion-selective electrodes (ISEs) was developed to maintain nutrient solutions in closed-loop hydroponic systems within plant factories. Based on this monitoring system, an algorithm and individual ion supplementation system were developed to calculate the optimal amounts of ion replenishment for crop growth. The developed algorithms adopt distinct cost functions to achieve their respective goals. The ion balance-prioritized algorithm minimizes the cost function, which is defined as the sum of the squared differences between the target ion concentrations and the calculated ion concentrations. In contrast, the carbon emission reduction algorithm minimizes the cost function defined as the total carbon emissions, which are calculated by multiplying the individual salt supplementation amounts by their respective carbon emission coefficients. Simulation results demonstrated that the ion balance-prioritized algorithm achieved average errors of 5.5 ± 5.5%, 0.4 ± 0.5%, and 5.0 ± 11.2% for Ca, NO3, and K, respectively, showing superior performance in maintaining ion balance. Meanwhile, the carbon emission reduction algorithm achieved a total of 0.064 kg CO2, representing a 50.19% reduction compared to the ion balance-prioritized type. The developed algorithms and system are expected to reduce costs by minimizing nutrient and water usage through the recycling of waste nutrient solutions. Furthermore, they are anticipated to improve crop productivity by maintaining an optimal ion composition and to contribute to sustainable agriculture through carbon emission reduction.